Application of the Explosion Temperature for Estimation of Detonating Power of Multicomponent Explosives - Hossein Keshavarz, Mohammad; Reza Pouretedal, Hamid (Asian Journal of Chemistry, 2010)
A method is reported here for predicting the Chapman-Jouguet detonation pressure of multicomponent explosives at any loading density. It is assumed that the explosive reacts to form major products composed of C(s), CO, N2, H2O, H2 and CO2 as determined by the oxygen balance of the unreacted explosive. Detonation pressure can be related to the temperature of explosion, the number of moles of gaseous products and initial density of the explosive. Explosion temperature based on the assumed decomposition reaction, as a fundamental parameter, can be easily found from the condensed heat of formation of the explosive and molar heat capacity of the gaseous products. Good agreement is obtained between measured and calculated values of detonation pressure for well known mixture of explosives at any initial density defined by experiment as compared to complex computer code.